Importance of the Cys124−Cys128 intermolecular disulfide bonding for oligomeric assembly and hemolytic activity of the Helicobacter pylori TlyA hemolysin - Nitchakan Samainukul (2019)
© 2019 Elsevier Inc. Although the TlyA hemolysin from Helicobacter pylori has been implicated as a potential virulence factor involved in mediating host cell colonization and hence disease progression, its structural determinants underlying the biological activity are still largely uncertain. In this study, an important role of the formation of a particular disulfide bond for functional oligomeric assembly of the H. pylori TlyA toxin was evidently elucidated. The 27-kDa TlyA recombinant protein was overexpressed in Escherichia coli, subsequently purified to near homogeneity by cation exchange chromatography, and proven to be hemolytically active against sheep erythrocytes. Additionally, TlyA-induced hemolytic activity was significantly diminished under conditions of disulfide bond reduction with a thiol-reducing agent, dithiothreitol. When the purified TlyA protein was subjected to modified SDS-PAGE under non-reducing conditions, the presence of an oligomeric state of this protein was clearly revealed by its apparent molecular mass of ∼48 kDa. Recombinant E. coli cells expressing TlyA also displayed contact-dependent hemolysis of erythrocytes, suggesting TlyA localization at the bacterial outer membrane and thus supporting the formation of disulfide-bonded TlyA. Homology-based modeling and in silico structural assembly analysis of TlyA signified potential intermolecular, rather than intramolecular, disulfide bonding through Cys124 and Cys128. Subsequently, single substitution of either of these Cys residues with Ser severely affected the oligomeric assembly of both TlyA mutants and hence abolished their hemolytic activity. Altogether, our present data provide pivotal evidence that the formation of intermolecular disulfide bonding between Cys124 and Cys128 plays a critical role in structural assembly of a biologically active-TlyA oligomer.